The Complexities of Neutrality in Teaching Religious Education: The Ethics and Religious Culture Program as Case Study - Zaver, Arzina (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2015)
In 2008, the Québec Ministry of Education introduced the Ethics and Religious Culture (ERC) program. Though the ERC is a positive step forward in promoting and fostering much-needed religious literacy skills, the implications of a “neutral” professional posture asked of its teachers have been difficult to translate into the classroom. Neutrality is seen to infringe on a teacher’s sense of autonomy and authenticity. This article traces the concept of neutrality in Québec back to the state policies, showing that neutral pedagogy contradicts the ethics of religious sensitivity and religious literacy that Québec is seemingly promoting. It concludes by offering a more balanced approach to the teaching of religion in the classroom.